مسوغات الدعوة للصناعات الصغيرة و المتوسطة : دراسة نظرية تحليلية - عبد العزيز مصطفى عبد الكريم (PROSPECTIVE RESEARCHES, 2023)
Small & medium size industries have developed in most industrial countries. They became in the last two decades employing advanced technology in addition to participating in the production of most specialized goods. So that, these industries succeed in achieving their goals and participating actively in strengthening national economy. The problem of the research is that industries in most developing countries, especially Arab countries are unable to achieve their goals. Depending on the analytical approach we concentrated on the feature and characteristics of small and medium size industries and the ways to support them.